The girl from the other side : Siúil, a Rún. Vol. 3 - Nagabe; MacFarlane, Ysabet Reinhardt (Girl from the Other side, Siuil, a Run ;, 2017)
"Shiva's aunt has come to the Outside to bring her home, with several soldiers in tow. Alarmed at this show of force, Teacher tries to protect Shiva, but to no avail. Meanwhile, chaos threatens to engulf the small hamlet on the Inside. Where does Shiva truly belong?--